2023
DOI: 10.3390/buildings13061360
|View full text |Cite
|
Sign up to set email alerts
|

The Current Development of Structural Health Monitoring for Bridges: A Review

Abstract: The health monitoring system of a bridge is an important guarantee for the safe operation of the bridge and has always been a research hotspot in the field of civil engineering. This paper reviews the latest progressions in bridge health monitoring over the past five years. This paper is organized according to the various links of the bridge health monitoring system. Firstly, the literature on monitoring technology is divided into two categories, sensor technology and computer vision technology, for review. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 200 publications
0
29
0
Order By: Relevance
“…The Internet of Things (IoT) and artificial intelligence (AI) are related to this technology. Furthermore, the expert system can be adopted for civil engineering purposes [13], [41], [54], [55]. The development of expert systems covers user interfaces, knowledge bases, engine interfaces, and development engines [12], [48], [52], [54].…”
Section: A Structural Health Monitoring System (Shms)mentioning
confidence: 99%
“…The Internet of Things (IoT) and artificial intelligence (AI) are related to this technology. Furthermore, the expert system can be adopted for civil engineering purposes [13], [41], [54], [55]. The development of expert systems covers user interfaces, knowledge bases, engine interfaces, and development engines [12], [48], [52], [54].…”
Section: A Structural Health Monitoring System (Shms)mentioning
confidence: 99%
“…In recent years, both civil construction and the building sector have explored the utilization of sensing technologies for SHM embedded in their structure [6,7]; in particular, focus has been given to the SHM of bridges [8,9]. However, the integration of sensors into non-load-bearing structures, such as a curtain wall façade, represents an increasing topic that needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, modal parameters can be used to evaluate the safety condition of a structure and assess structural health based on modal parameters [25]. Deng et al [9] demonstrated that temperature is an important factor that affects the natural frequency of the bridge, and it is not negligible. Therefore, the temperature must be controlled in order to not consider a variation in frequency only due to temperature change as a damage indicator.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it remains crucial to continue conducting research and employing innovative approaches to minimize the occurrence of such accidents and their detrimental consequences. In an effort to enhance the safety and reliability of bridges and minimize the incidence of bridge collapse accidents, numerous scholars and experts have conducted comprehensive statistical investigations into the causes of bridge collapses [13][14][15]. The study of bridge collapse encompasses several disciplines, such as structural engineering, monitoring technology [16,17], transportation, and earthquake engineering, among others, and research methods employed in this area include theoretical analysis, experimental testing, numerical simulation, and case studies.…”
Section: Introductionmentioning
confidence: 99%